Real-world characteristics, treatment patterns, and outcomes in advanced HER2 (ERBB2)-mutant non-small cell lung cancer: a retrospective study of single centers in France and Germany - Christopoulos, Petros; Assmann, Christin; Zhang, Lirong; Dunton, Kyle; Ali, Ahmed; Berktas, Mehmet; Delmastro, Lisa; Strübing, Alessandria; Xiong, Yan; Lay-Flurrie, Sarah; Hindocha, Pooja; Mehdikhanova, Tarana; et al. (Clinical therapeutics, 2025)
Purpose - Human epidermal growth factor receptor 2 (HER2 [ERBB2]) gene mutations occur in ∼3-5% of non-small cell lung cancer (NSCLC) cases and are associated with poor prognosis. However, real-world data on patients with HER2-mutant (HER2m) NSCLC are needed. - Methods - This retrospective, observational study evaluated characteristics, treatment patterns, and clinical outcomes of patients with advanced nonsquamous HER2m NSCLC from the Institut Curie (France) and Thoraxklinik Heidelberg (Germany) between 2011 and 2022. - Findings - Of the 55 patients (Curie: n = 17; Heidelberg: n = 38) included in the study, median age at diagnosis was 66 years (range, 22-90), 63.6% were female, and 50.9% had no history of smoking. Forty-eight (87.3%) patients received ≥1 line of therapy, 29 (52.7%) received ≥2 lines of therapy, and 19 (34.5%) received ≥3 lines of therapy. The most common first-line treatment was platinum-based and non-platinum-based chemotherapy (54.2%, n/n = 26/48); treatment patterns in the second- and third-line settings were more diverse than in the first-line setting. Median overall survival was 14.2 months (95% confidence interval [CI] 11.2, 23.2; n = 55) from the diagnosis of advanced disease and 16.5 months (12.3, 29.8; n = 48) from the start of first-line treatment. Median progression-free survival was 5.1 months (95% CI 3.5, 8.5; n = 48) and 4.0 months (2.4, 6.3; n = 29) from the start of first- and second-line treatment, respectively. - Implications - Patients with advanced HER2m NSCLC had a poor prognosis despite treatment with standard-of-care regimens available during the study period. These findings highlight the need for novel therapeutic options to improve clinical outcomes for patients with HER2m NSCLC.
Online verfügbar: 1. November 2025, Artikelversion: 29. November 2025
Gesehen am 12.02.2026